Effect of dietary substitution of sea tangle (ST), Laminaria japonica with rice bran (RB) on growth and body composition of juvenile abalone (Haliotis discus). (4th September 2014) - Kim, Ye Eun; Myung, Sung Hyo; Kim, Hee Sung; Jung, Won‐Gwan; Cho, Sung Hwoan; Jwa, Min Seok; Kim, Pil Youn; Kim, Mun Kwan; Park, Min‐Woo; Kim, Byeng‐Hak
Abstract: Dietary substitution effect of sea tangle (ST) with rice bran (RB) on growth and carcass composition of juvenile abalone ( Haliotis discus ) was determined. Juvenile abalone was acclimated to the experimental conditions for 4 weeks. Seventy juvenile abalone averaging 0.43 g were randomly distributed into each of the 18, 70 L plastic rectangular containers. The experimental diets were fed to abalone once a day at a satiation level with a little leftover. The feeding trial lasted for 16 weeks. Survival of abalone was not affected by dietary substitution of ST with RB. However, weight gain of abalone fed the RB40 diet was higher than that of abalone fed the all other diets except for the RB0 diet. No significant difference in weight gain was found in abalone fed between the RB0 and RB100 diets. SGR of abalone fed the RB40 diet was higher than that of abalone fed the all other diets. Also SGR of abalone fed the RB0 diet was higher than that of abalone fed the RB100 diet, but not different from that of abalone fed the RB20, RB60 and RB80 diets. Moisture, crude protein and ash content of the soft body of abalone were affected by dietary substitution of ST with RB. In conclusion, the 100% ST could be substituted with RB without a retardation of weight gain of abalone when the 20% ST was included into the experimental diet. However, the best growth performance was obtained in abalone fed the RB40 diet substituting 40% ST with RB.